2018
DOI: 10.1093/jbcr/irx011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bromelain-Based Enzymatic Debridement on Skin Cells

Abstract: Several reports have concluded that enzymatic debridement based on Bromelain (NX) is selective and efficient. Although clinical trials showed that viable tissue is not damaged at the macroscopic level, the effect on the cellular level is largely unknown. The current study is meant to close this gap by evaluating whether NX has an effect on vital cells of the human dermis on a cellular level. In an experimental in vitro study design, the effect of NX on human keratinocytes, fibroblasts, and macrophages was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Still, other studies have shown that different preparations of bromelain could induce cell cycle arresting in G0 phase (quiescence), which would explain the inhibition of cell proliferation 39 . These results reinforce the understanding that the healing effect of bromelain in wound care is mainly due to its debriding action, which removes cell debris and necrotic tissues in vivo, in accordance with other studies 6 , 38 , 40 , 41 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Still, other studies have shown that different preparations of bromelain could induce cell cycle arresting in G0 phase (quiescence), which would explain the inhibition of cell proliferation 39 . These results reinforce the understanding that the healing effect of bromelain in wound care is mainly due to its debriding action, which removes cell debris and necrotic tissues in vivo, in accordance with other studies 6 , 38 , 40 , 41 .…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the proteolytic action of bromelain could be affecting cells more directly than in the condition of cultivation with medium supplemented with 5% FBS. A similar effect was reported by Schulz et al 38 when comparing the effect of a formulation containing bromelain on the viability of human fibroblasts and keratinocytes (primary cultures) in complete culture medium or in phosphate-buffered saline (PBS). The replacement of culture medium with PBS intensified the cytotoxic effect of bromelain on both cells evaluated.…”
Section: Discussionsupporting
confidence: 76%
“…[186]. It is worth noting that Schulz et al [187] and Berner et al [188] pay attention to the low selectivity of the bromelain-based enzymatic debridement (NexoBrid ® ), which has a toxic effect on viable human skin cells, especially at high concentrations.…”
Section: Enzymatic Debridement and Pro-wound Healing Activitiesmentioning
confidence: 99%
“…The early removal of necrotic eschar represents the standard in modern burn therapy in order to reduce or prevent local infection, sepsis, scarring, or other complications and allow proper wound bed evaluation. Enzymatic debridement offers a needs-based technique with a maximum of healthy tissue conservation by providing a selective and sparing concept for necrotic tissue ablation [25][26][27]. The application of plant-based agents such as resin, honey, or other herbal remedies on burn wounds was already described in ancient Egypt (1600 BC) [28].…”
Section: Enzymatic Debridementmentioning
confidence: 99%